# Solve for y 2/y=3/(y-2)-1

2y=3y-2-1
Find the LCD of the terms in the equation.
Finding the LCD of a list of values is the same as finding the LCM of the denominators of those values.
y,y-2,1
Since y,y-2,1 contain both numbers and variables, there are four steps to find the LCM. Find LCM for the numeric, variable, and compound variable parts. Then, multiply them all together.
Steps to find the LCM for y,y-2,1 are:
1. Find the LCM for the numeric part 1,1,1.
2. Find the LCM for the variable part y1.
3. Find the LCM for the compound variable part y-2.
4. Multiply each LCM together.
The LCM is the smallest positive number that all of the numbers divide into evenly.
1. List the prime factors of each number.
2. Multiply each factor the greatest number of times it occurs in either number.
The number 1 is not a prime number because it only has one positive factor, which is itself.
Not prime
The LCM of 1,1,1 is the result of multiplying all prime factors the greatest number of times they occur in either number.
1
The factor for y1 is y itself.
y1=y
y occurs 1 time.
The LCM of y1 is the result of multiplying all prime factors the greatest number of times they occur in either term.
y
The factor for y-2 is y-2 itself.
(y-2)=y-2
(y-2) occurs 1 time.
The LCM of y-2 is the result of multiplying all factors the greatest number of times they occur in either term.
y-2
The Least Common Multiple LCM of some numbers is the smallest number that the numbers are factors of.
y(y-2)
y(y-2)
Multiply each term by y(y-2) and simplify.
Multiply each term in 2y=3y-2-1 by y(y-2) in order to remove all the denominators from the equation.
2y⋅(y(y-2))=3y-2⋅(y(y-2))-1⋅(y(y-2))
Simplify 2y⋅(y(y-2)).
Cancel the common factor of y.
Cancel the common factor.
2y⋅(y(y-2))=3y-2⋅(y(y-2))-1⋅(y(y-2))
Rewrite the expression.
2⋅(y-2)=3y-2⋅(y(y-2))-1⋅(y(y-2))
2⋅(y-2)=3y-2⋅(y(y-2))-1⋅(y(y-2))
Apply the distributive property.
2y+2⋅-2=3y-2⋅(y(y-2))-1⋅(y(y-2))
Multiply 2 by -2.
2y-4=3y-2⋅(y(y-2))-1⋅(y(y-2))
2y-4=3y-2⋅(y(y-2))-1⋅(y(y-2))
Simplify 3y-2⋅(y(y-2))-1⋅(y(y-2)).
Simplify each term.
Cancel the common factor of y-2.
Factor y-2 out of y(y-2).
2y-4=3y-2⋅((y-2)y)-1⋅(y(y-2))
Cancel the common factor.
2y-4=3y-2⋅((y-2)y)-1⋅(y(y-2))
Rewrite the expression.
2y-4=3⋅y-1⋅(y(y-2))
2y-4=3⋅y-1⋅(y(y-2))
Apply the distributive property.
2y-4=3y-1⋅(y⋅y+y⋅-2)
Multiply y by y.
2y-4=3y-1⋅(y2+y⋅-2)
Move -2 to the left of y.
2y-4=3y-1⋅(y2-2⋅y)
Apply the distributive property.
2y-4=3y-1y2-1(-2y)
Rewrite -1y2 as -y2.
2y-4=3y-y2-1(-2y)
Multiply -2 by -1.
2y-4=3y-y2+2y
2y-4=3y-y2+2y
2y-4=-y2+5y
2y-4=-y2+5y
2y-4=-y2+5y
Solve the equation.
Since y is on the right side of the equation, switch the sides so it is on the left side of the equation.
-y2+5y=2y-4
Move all terms containing y to the left side of the equation.
Subtract 2y from both sides of the equation.
-y2+5y-2y=-4
Subtract 2y from 5y.
-y2+3y=-4
-y2+3y=-4
Move 4 to the left side of the equation by adding it to both sides.
-y2+3y+4=0
Factor the left side of the equation.
Factor -1 out of -y2+3y+4.
Factor -1 out of -y2.
-(y2)+3y+4=0
Factor -1 out of 3y.
-(y2)-(-3y)+4=0
Rewrite 4 as -1(-4).
-(y2)-(-3y)-1⋅-4=0
Factor -1 out of -(y2)-(-3y).
-(y2-3y)-1⋅-4=0
Factor -1 out of -(y2-3y)-1(-4).
-(y2-3y-4)=0
-(y2-3y-4)=0
Factor.
Factor y2-3y-4 using the AC method.
Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -4 and whose sum is -3.
-4,1
Write the factored form using these integers.
-((y-4)(y+1))=0
-((y-4)(y+1))=0
Remove unnecessary parentheses.
-(y-4)(y+1)=0
-(y-4)(y+1)=0
-(y-4)(y+1)=0
Multiply each term in -(y-4)(y+1)=0 by -1
Multiply each term in -(y-4)(y+1)=0 by -1.
(-(y-4)(y+1))⋅-1=0⋅-1
Simplify (-(y-4)(y+1))⋅-1.
Simplify by multiplying through.
Apply the distributive property.
(-y–4)(y+1)⋅-1=0⋅-1
Multiply -1 by -4.
(-y+4)(y+1)⋅-1=0⋅-1
(-y+4)(y+1)⋅-1=0⋅-1
Expand (-y+4)(y+1) using the FOIL Method.
Apply the distributive property.
(-y(y+1)+4(y+1))⋅-1=0⋅-1
Apply the distributive property.
(-y⋅y-y⋅1+4(y+1))⋅-1=0⋅-1
Apply the distributive property.
(-y⋅y-y⋅1+4y+4⋅1)⋅-1=0⋅-1
(-y⋅y-y⋅1+4y+4⋅1)⋅-1=0⋅-1
Simplify and combine like terms.
Simplify each term.
Multiply y by y by adding the exponents.
Move y.
(-(y⋅y)-y⋅1+4y+4⋅1)⋅-1=0⋅-1
Multiply y by y.
(-y2-y⋅1+4y+4⋅1)⋅-1=0⋅-1
(-y2-y⋅1+4y+4⋅1)⋅-1=0⋅-1
Multiply -1 by 1.
(-y2-y+4y+4⋅1)⋅-1=0⋅-1
Multiply 4 by 1.
(-y2-y+4y+4)⋅-1=0⋅-1
(-y2-y+4y+4)⋅-1=0⋅-1
(-y2+3y+4)⋅-1=0⋅-1
(-y2+3y+4)⋅-1=0⋅-1
Apply the distributive property.
-y2⋅-1+3y⋅-1+4⋅-1=0⋅-1
Simplify.
Multiply -y2⋅-1.
Multiply -1 by -1.
1y2+3y⋅-1+4⋅-1=0⋅-1
Multiply y2 by 1.
y2+3y⋅-1+4⋅-1=0⋅-1
y2+3y⋅-1+4⋅-1=0⋅-1
Multiply -1 by 3.
y2-3y+4⋅-1=0⋅-1
Multiply 4 by -1.
y2-3y-4=0⋅-1
y2-3y-4=0⋅-1
y2-3y-4=0⋅-1
Multiply 0 by -1.
y2-3y-4=0
y2-3y-4=0
Factor y2-3y-4 using the AC method.
Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -4 and whose sum is -3.
-4,1
Write the factored form using these integers.
(y-4)(y+1)=0
(y-4)(y+1)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
y-4=0
y+1=0
Set the first factor equal to 0 and solve.
Set the first factor equal to 0.
y-4=0
Add 4 to both sides of the equation.
y=4
y=4
Set the next factor equal to 0 and solve.
Set the next factor equal to 0.
y+1=0
Subtract 1 from both sides of the equation.
y=-1
y=-1
The final solution is all the values that make (y-4)(y+1)=0 true.
y=4,-1
y=4,-1
Solve for y 2/y=3/(y-2)-1

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top